Pulse rate and Spo2 in different phases of menstrual cycle in healthy women of Kerala - Kumar, SS; George, J; Mohamed, JVK; Divya, Dr; Jose, A; Mukkadan, JK (Janaki Medical College Journal of Medical Science, 2013)
Background and Objectives: The studies on relationship between different phases of menstrual cycle and pulse rate and Sp02 changes in healthy women of Kerala are inadequate. So, this preliminary study was plan to report the same. Material and Methods: The present study was performed in twenty healthy women of Kerala, age ranging from 20-40 (mean age 27+/- 61054). Spo2 and pulse rate were recorded with pulse - oximeter in different phases of menstrual cycle and analysis of data was done by spss 20.0. Results: Variations of pulse rate and Spo2 in different phases of menstrual cycle are not statistically significant at p > 0.05. Conclusion: it was observed that there was slight increase in pulse rate in ovulatory phase and slight increase in Sp02 in secretory phase, though it is not statistically significant. It may be due to small sample size. Hence this study certainly merits continuing the work with more investigations in the field. Janaki Medical College Journal of Medical Sciences (2013) Vol. 1 (2): 65-69 DOI: http://dx.doi.org/10.3126/jmcjms.v1i2.9271